Integrated Performance Assessment Instrument of Tri Hita Karana's Priority Values in Vocational Learning - Putu Agus Mayuni; I Gede Sudirtha; Ni Ketut Widiartini; Made Diah Angendari (Mimbar Ilmu, 2023)
This study aims to analyze the success of developing an integrated performance assessment instrument for the priority values of Tri Hita Karana (THK) in vocational learning, in this case, in the practicum course for making men's clothing. This type of research is development research, which was developed using the ADDIE model. The subjects in this study were colleagues and learning and assessment experts. The focus of the research was the development of an integrated portfolio assessment instrument of the priority values of Tri Hita Karana in the practicum course in the manufacture of menswear. Data collection in this study was carried out using the method of questionnaires, with the research instrument being a validity sheet. The data obtained in the study were then analyzed using data analysis techniques using quantitative descriptive analysis. The feasibility of the resulting set of instruments is tested for validation using the Gregory formula using two experts and testing the reliability of the instrument using the inter-rater reliability technique. The results showed that the developed performance assessment instrument met the validity criteria with an average 4.0 (relevant) score and obtained very high validity through calculations using the Gregory formula (1.0). Calculation of reliability through an inter-rater agreement from two experts, which was very consistent with a score on the performance instrument of 0.96. Based on these results, it can be concluded that the design of the integrated performance assessment instrument set of priority values of Tri Hita Karana karana in the Men's Clothing Making Practical Course developed is in the valid and reliable category, so it is very feasible to use to measure students' abilities.